Recent Advances in Earthquake Engineering Select Proceedings of VCDRR 2021 - Kolathayar, Sreevalsa; Chian, Siau Chen.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book presents the select proceedings of the Virtual Conference on Disaster Risk Reduction (VCDRR 2021). It emphasizes on the role of civil engineering for a disaster-resilient society. It presents latest research in geohazards and their mitigation. Various topics covered in this book are earthquake hazard, seismic response of structures and earthquake risk. This book is a comprehensive volume on disaster risk reduction (DRR) and its management for a sustainable built environment. This book will be useful for the students, researchers, policy makers and professionals working in the area of civil engineering and earthquake engineering. .
Keywords: Environmental engineering; Civil engineering; Natural disasters; Geotechnical engineering; Environmental Civil Engineering; Natural Hazards; Geotechnical Engineering and Applied Earth Sciences; Earthquake engineering -- Congresses; Hazard mitigation -- Congresses